Identification of the intermediate host of Gongylonema sp., the etiological agent of the necrotic oropharyngeal disease of the Scops owl (Otus scops). (February 2022) - Lopes, F.; Esperón, F.; Bravo-Barriga, D.; Frontera, E.; Cabrero-Sañudo, F.J.; Gil-Tapetado, D.; Orejas, P.; Alonso, R.
Abstract: Since 1997, fledgling Scops owls (Chordata: Strigidae) have been brought to the Brinzal Owl Rescue Centre (Madrid, Spain) with severe lesions in their oral cavities. Lesions consist of the presence of proliferative necrotic material in the oral cavity resulting in white plaques, which can lead to death by starvation. This disease has been detected in owls only within the limits of the city of Madrid. The etiologic agent has been identified as Gongylonema sp. (Nematoda: Spirurida), a nematode genus that includes a coprophagous arthropod as intermediate host in its cycle. The aim of this study was to identify the intermediate host of the parasite. Our work was structured in four component phases: i) Diet study of newborn chicks; ii) trapping arthropods that could be intermediate hosts; iii) molecular detection of the parasite in the selected arthropods: and iv) molecular characterization of the detected parasites by amplifying the cox1 gene. Four male owls were radio-tagged in order to locate their nests and a camera trap was placed to identify the prey brought to the owlets. Secondly, the arthropods present in the hunting areas of the owls were sampled, identified and analyzed by real time PCR (rtPCR). Only oriental cockroaches, B. orientalis (Arthropoda: Blattodea), were positive by rtPCR detection of Gongylonema sp. (66.7%). The nematodes obtained from cockroaches had a 99.8% identity of the cox1 gene with the Gongylonema sp. isolated for the first time in a Scops owl. Furthermore, these sequences only showed an <89% identity with all the other Gongylonema sequences available in the GenBank database. We conclude that the oriental cockroach should be considered as an intermediate host of the etiologic agent of NOD. Graphical abstract: Unlabelled Image Highlights: Cockroaches ( Blata orientalis ) are the most available prey for the scops owls in the green areas of Madrid City. Blata orientalis was the only sampled invertebrate positive to Gongylonema sp. in the PCR analyses. Blata orientalis and should be considered as the most likely intermediate host of Gongylonema sp. for the scops owl in the city of Madrid.